Global trends of libraries development: optimism vs pessimism (foreign literature review) Part 1 - N. S. Redkina (Библиосфера)
The dynamic development of the external technological environment, on the one hand, impacts on libraries questioning their future existence, on the other, helps libraries to work more productively, increases competitiveness and efficiency, expands the range of social projects, develops new ways and forms of work with users taking into account their preferences in information and services. The review is based on over 500 articles searched in the world's largest databases (Google Scholar, Web of Science, Scopus, etc.), which discuss trends and future development of libraries. Then the documents were classified according to sections and types of libraries, as well as advanced technologies. Examples of information technologies were collected and reviewed, as well as articles related to the implementation of information technologies when creating new services, with the emphasis on those that may affect libraries in the future. The latest information technologies that can be applied to the next generation library have been studied. The material is structured in blocks and presented in two parts. Thie 1st one presents such sections as: 1) challenges of the external environment and the future of libraries, 2) modern information technologies in libraries development (mobile technologies and applications, cloud computing, big data, internet of things, virtual and augmented reality, technical innovations, etc.), 4) Library 4.0 concept - new directions for libraries development. The 2nd part of the review article (Bibliosphere, 2019, 1) will touch the following issues: 1) user preferences and new library services (software for information literacy development, research data management, web archiving, etc.), 2) libraries as centers of intellectual leisure, communication platforms, places for learning, co-working, renting equipment, creativity, work, scientific experiments and leisure, 3) smart buildings and smart libraries, 4) future optimism. Based on the content analysis of publications, it is concluded that libraries should not only accumulate resources and provide access to them, but renew existing approaches to forms and content of their activities, as well as goals, missions and prospects for their development using various hard- and software, cloud computing technologies, mobile technologies and apps, social networks, etc.